Incompatibility among drugs and the materials of intravenous therapy catheters and disposable accessories. Descriptive study - Maria Angélica Sorgini Peterlini; Massae Noda Chaud; Mavilde LG Pedreira (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
Objective: To identify to the occurrence of incompatibility among drugs and the materials of intravenous therapy catheters and disposable accessories in hospitalized children. Method: Descriptive research related to the incompatibility among drugs and manufacture material of catheters and disposable accessories of the intravenous therapy prescribed to children, hospitalized in four pediatric wards of a university hospital. The data collection was realized through the structured observation of nursing staff practice during the intravenous therapy execution. Results: A total of 519 executions of intravenous therapy were observed in 178 children. The drugs were infused by 209 catheters, made of vialon, Teflon, stainless steel and polyurethane, being incompatibles 3.1% of the associations and in 96.9% no data was available in the literature regarding this issue. The polyvinyl chloride was the material verified in all (601) disposable accessories and 60.7% associations were compatibles, 19.8% incompatibles and for 19.5% of the associations, scientific evidences were not identified to support this nursing practice.